Theileria parva carrier state in naturally infected and artificially immunized cattle - Kariuki, D.P.; Young, A.S.; Morzaria, S.P.; Lesan, A.C.; Mining, S.K.; Omwoyo, P.; Wafula, J.L.M.; Molyneux, D.H. (Springer, 1995)
Rhipicephalus appendiculatus adult ticks, collected int he field from zebu (Bos indicus) and exotic (Bos tarus) cattle with high antibody titres to Theileria parva schizont antigen, transmitted Theileria parva infection typical of East Coast fever to susceptible cattle. Uninfected R. appendiculatus nymphs applied to naturally recovered zebu and exotic cattle kept under tick-free conditions in the laboratory for 16 and 7 months respectively, transmitted fatal theileriosis to susceptible cattle. Cattle immunised by the infection and treatment method were shown to be carriers of Theileria parva by examination of the salivary glands of ticks applied to them and by tick transmission. Three and 7 monts after immunisation, Theileria parva infected lymphocytes were established in vitro from peripheral blood lymphocytes. This was the first demonstration, in vitro, of the existence of schizonts in Theileria parva (East Coast fever) infection carrier status. These studies show that cattle from endemic and epidemic areas of East Coast fever (ECF) become carriers thereby maintaining the T. parva population. The relevance of the findings in this study to the control of ECF by dipping, immunisation and treatment is discussed.